Theoretical Study of Multiple Solar Cells System as a Function of Temperature - Ben Slimane Hassane; Ben Moussa Dennai; Helmaoui Abderrachid (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
A simulation model has been performed on materials as Ge, Si, GaAs, AlGaAs and the values of gaps Egk of hypothetical materials, the calculation of the corresponding maximum efficiency was carried out for multigap solar cells systems coupled in splitting mode. The effects of an optical coupling by a dichroic mirror between independent solar cells, and solar cells coupled in series has been analysed. One particular result of our study is that the coupling by a dichroic mirror between an independent cell gives an interesting efficiency.